ANALYSIS OF MACHINE TRANSLATION IN CULTURAL TRANSLATION OF JAVANESE FOLK SONGS - Latifah Aura Billah; Masduki Masduki (Journal of Social, Culture, and Language, 2025)
This research analyzes the lyrics of Javanese folk songs, “Rek Ayo Rek” and “Lir Ilir” translated by Machine Translation, namely Google Translate. The folk songs convey cultural messages that require contextual understanding. This study evaluates the equivalence and accuracy of the translations produced, and identifies the errors that occur in the translation process.This study uses Eugene Nida's Dynamic Equivalence theory which aims to evaluate the extent to which Machine Translation can maintain the original meaning of Javanese culture. The analysis shows that the translations are structurally correct, but often miss important idioms and cultural nuances. The analysis showed that 83% of the translations in “Rek Ayo Rek” lyrics and 100% in “Lir Ilir” lyrics lost symbolism and cultural meaning due to literal translation. The findings show incomplete translations, word misinterpretation, and loss of cultural nuances, indicating the limitations of Machine Translation in translating cultural aspects. This study contributes to the development of more effective folk song translation strategies, especially in translating texts that contain cultural context.Keywords : Folk Songs, Google Translate, Lyrics, Machine Translations.